Pengaruh Penerimaan Pajak Terhadap Variabel Pendapatan Perkapita dan Angka Kemiskinan Sebagai Indikator Kemakmuran Rakyat - Iman Akhadi (JURNAL PAJAK INDONESIA, 2022)
The aim of the research is to examine the Effect of Realized Tax Revenue on Poverty Rates and Per capita Income as an Indicator of People's Prosperity, using the mediating variables for Transfer Expenditures to Regions and the Subsidy Budget Program in the Indonesian National Budget for the 2010-2020 period. The research method was carried out through simple regression analysis using data sourced from BPS and the Indonesian National Budget for the 2010-2020 period. The data is then analyzed to test the research hypothesis through classical assumption test and simple regression testing. The results showed that the realization of tax revenues had a significant negative effect on the poverty rate and a significant positive effect on per capita income. The variable of Expenditure Transfers to the Regions was proven to be significantly a complete mediation variable, while the Subsidized Budget Program variable was not a mediating variable. The limitations of this study are indicators for measuring people's prosperity in the form of GDP Per capita and Poverty Rates in Indonesia during the 2010-2020 period. Other variables are not used as indicators to measure people's prosperity, for example the Human Development Index (HDI), the Development Equity Index, etc. Through this research, it is hoped that the taxpayers will increasingly understand the importance of taxes in order to increase the prosperity of the people. This is at the same time to prove the meaning of tax as a means to increase people's prosperity. Tujuan penelitian ini adalah untuk menguji Pengaruh Realisasi Penerimaan Pajak Terhadap Angka Kemiskinan dan Pendapatan Perkapita sebagai Indikator Kemakmuran Rakyat. Metode penelitian dilakukan melalui analisis regresi sederhana dengan menggunakan data yang bersumber dari BPS dan APBN RI selama periode 2010-2020. Data tersebut kemudian dianalisis untuk menguji hipotesis penelitian melaui uji asumsi klasik dan uji regresi sederhana. Hasil penelitian menunjukkan bahwa Realisasi Penerimaan Pajak berpengaruh signifikan negatif terhadap Angka Kemiskinan serta berpengaruh signifikan positif terhadap Pendapatan Perkapita. Variabel Belanja Transfer ke Daerah terbukti secara signifikan merupakan variabel mediasi sempurna (complete mediation), sedangkan variabel Program Anggaran Subsidi bukan merupakan variabel mediasi. Keterbatasan dari penelitian ini adalah indikator untuk mengukur kemakmuran rakyat berupa PDB Perkapita dan Angka Kemiskinan di Indonesia selama periode 2010-2020. Adapun variabel lainnya tidak dijadikan sebagai indikator untuk mengukur kemakmuran rakyat, misalnya Indeks Pembangunan Manusia (IPM), Indeks Pemerataan Pembangunan, dll. Melalui penelitian ini, diharapkan masyarakat semakin memahami pentingnya pajak dalam rangka meningkatkan kemakmuran rakyat. Hal ini sekaligus untuk membuktikan pengertian pajak sebagai sarana untuk meningkatkan kemakmuran rakyat.